PENGARUH INFORMASI AKUNTANSI DALAM PENGAMBILAN KEBIJAKAN KEUANGAN PEMERINTAH DAERAH (STUDI PADA PEMERINTAH KOTA KENDARI) - Nurnaluri, Sitti; Awaluddin, Ishak; Ansar, Rio Rizky (JURNAL AKUNTANSI DAN KEUANGAN, 2018)
Â ABSTRACTThis study aimed to investigate the effect of accounting information in the governmentâs financial policy making in Kendari City. The object of this studyis the financial Management Agency And Regional Assets in Kendari City. Instrument in this study was throuh a questionnaire to the parties concerned. Â Researchers Â alsoÂ  collectedÂ  relevant Â document Â andÂ  research Â to support the discussion. The testing technique are performed in a simple linier regression analysis. This study found that the effect of accounting information in decisionÂ  Â makingÂ Â  ofÂ  Â localÂ  Â governmentÂ  Â finance in Kendari City. In formulating Â financial Â policy, Â the Â government Â is Â also Â considering Â theÂ  vision, mission, goals, and objectives, so that any policies made by the government to achieve the ultimate goal of local government.Keywords : : accounting information, Making financial policy, government..